OC-096 TH17 cells are increased in Helicobacter pylori infection and may be associated with peptic ulcer disease. (28th May 2012) - Staples, E; Ingram, R J M; Hussain, K; Letley, D P; Atherton, J C; Robinson, K
Abstract : Introduction: Helicobacter pylori ( Hp ) persistently colonises the stomachs of half the world's population. The majority of hosts remain asymptomatic but 10%–15% will develop peptic ulcer disease (PUD) or gastric cancer. Disease is associated with an IFNγ-producing T-helper 1 (Th1) response. Pro-inflammatory IL-17-producing T-helper 17 (Th17) cells, which express the transcription factor RORC2, are also likely to be involved. The murine Th17 response to Hp has been characterised but the role of human Th17 responses remains unclear. Aim: To assess the importance of Th17 cells in Hp + patients. We quantified Th17 cells in the human gastric mucosa, compared IL17, RORC2 and IFNG transcription, and investigated correlations with PUD. Methods: Gastric biopsies were donated by patients undergoing routine upper GI endoscopy at Queen's Medical Centre in Nottingham with informed consent and ethical approval. Patient characteristics: 17 with Hp −associated PUD, 28 with Hp -associated gastritis and 17 uninfected ( Hp −). Antral IL17 and RORC2 mRNA levels (all patient biopsies) and IFNG transcription (26 Hp + and 9 Hp − biopsies) and were quantified by real time PCR (RT-qPCR) relative to a comparator prepared from a further 14 uninfected biopsies. Frequencies of IL-17-secreting CD4 + and CD8 + T-cells were assessed by flow cytometry in gastric biopsies donated by 12 Hp + and 11 Hp − patients. Analysis: Comparisons between Hp + and Hp − groups and patients with and without PUD used Mann–Whitney tests. Levels of mRNA expression for paired biopsies were compared with Wilcoxon signed rank tests. Spearman's rank correlation was used to analyse relationships. Results: Increased frequencies of CD4 + IL-17 + Th17 (3.0-fold, p=0.001) and CD8 + IL-17 + (Tc17) cells (3.3-fold, p=0.01) were present in Hp + samples. RT-qPCR showed that infected patients have increased mucosal IL17 (45.0-fold, p<0.0001) and IFNG expression (3.4-fold, p=0.006) and showed for the first time that RORC2 expression was also higher (2.6-fold, p<0.0001). There was a trend towards a correlation between IL17 and IFNG expression (r=0.39, p=0.051) and relative IL17 expression was 3.1-fold higher than IFNG (p=0.0006). Relative RORC2 gene expression was also 35% higher in tissue from Hp + patients with PUD than in those with gastritis alone but this did not reach statistical significance (p=0.11). Conclusion: The Hp -infected human stomach has increased frequencies of Th17 and Tc17 cells, and increased expression of IL17, RORC2 and IFNG . IL17 expression was significantly higher than IFNG expression, though the sources of IL17 have yet to be fully characterised. There was a trend for increased RORC2 expression in PUD. Our data suggest that Th17 cell responses may influence the clinical outcome of Hp infection in patients. Competing interests: None declared.